The impact of high polymerization inulin on body weight reduction in high-fat diet-induced obese mice: correlation with cecal Akkermansia - Gan, Liping; Zhao, Yifeng; Zhang, Zongbao; Zhao, Chenkai; Li, Jiake; Jia, Qingyu; Shi, Yusu; Wang, Peng; Guo, Linna; Qiao, Hanzhen; Cui, Yaoming; Wang, Jinrong (Frontiers in Microbiology, 2024)
Obesity presents a significant public health challenge, demanding effective dietary interventions. This study employed a high-fat diet-induced obesity mouse model to explore the impacts of inulin with different polymerization degrees on obesity management. Our analysis reveals that high-degree polymerization inulin (HDI) exhibited a significantly higher oil binding capacity and smaller particle size compared to low-degree polymerization inulin (LDI) (p < 0.05). HDI was more effective than LDI in mitigating body weight gain in high-diet induced obese mice, although neither LDI nor HDI affected blood sugar levels when compared to the high-fat diet control group (p < 0.05). Both HDI and LDI administrations reduced liver weight and enhanced brown adipose tissue thermogenesis compared to the high-fat diet induced control group (p < 0.05). Additionally, HDI suppressed hepatic lipogenesis, resulting in a further reduction in liver triglycerides compared to the high-fat diet-induced obese mice (p < 0.05). Notably, HDI improved gut health by enhancing intestinal morphology and modulating gut microbiota structure. HDI administration notably increased the relative abundance of cecal Akkermansia, a gut microbe associated with improved metabolic health, while LDI showed limited efficacy (p < 0.05 and p > 0.05, respectively). These findings underscore the importance of the structural properties of inulin in its potential to combat obesity and highlight the strategic use of inulin with varying polymerization degrees as a promising dietary approach for obesity management, particularly in its influence on gut microbiota composition and hepatic lipid metabolism regulation.